Differential expression of CD57 in antigen-reactive CD4+ T cells between active and latent tuberculosis infection - Lee, Ji Yeon (Clinical immunology (Orlando, Fla.), 2015)
Copyright © 2015 Elsevier Inc. All rights reserved.